Usulan Rancangan Manajemen Risiko Pada Perusahaan Pelayaran PT XYZ Tahun 2021 – 2022 - Saifudin Saifudin; Aries Heru Prasetyo (PT Wim Solusi Prima, 2022)
PT XYZ is a private shipping company engaged in sea and river transportation services for coal transportation for domestic needs. The high demand for coal transportation services is the main capital for the company to continue to grow and develop as a company that plays a role in the energy industry sector on a national scale. Business competition in the shipping business is also increasing along with the growth in the number of national fleets, so companies must be pro-active in maintaining the performance of production equipment in order to maintain satisfaction from service users. The purpose of this qualitative research is to propose a risk management design for the shipping company PT XYZ using ISO 31000:2018 guidelines. Based on the assessment that has been carried out, 80 risks were identified from four categories; financial, operational, marketing, strategic, with the results showing that 2 risks are in the extreme category, 34 risks are in the high category, 44 risks are in the medium category. In order to protect the company from risk threats and ensure that the company's performance remains optimal based on effective and efficient working principles, it is necessary to apply risk management to the shipping company PT XYZ. PT XYZ adalah perusahaan pelayaran swasta yang bergerak dibidang jasa transportasi laut dan sungai untuk pengangkutan batubara kebutuhan dalam negeri. Tingginya kebutuhan jasa transportasi pengangkutan batubara menjadi modal utama bagi perusahaan untuk terus tumbuh dan berkembang sebagai perusahaan yang berperan dalam sector industry energi skala nasional. Persaingan usaha pada bisnis usaha pelayaran juga semakin meningkat seiring pertumbuhan jumlah armada nasional sehingga perusahaan harus pro aktif dalam menjaga kinerja alat produksi agar dapat menjaga kepuasan dari pengguna jasa. Tujuan dari penelitian yang bersifat kualitatif ini adalah mengusulkan rancangan manajemen risiko perusahaan pelayaran PT XYZ dengan menggunakan pedoman ISO 31000:2018. Berdasarkan asesmen yang telah dilakukan, maka teridentifikasi 80 risiko yang diperoleh dari empat kategori; keuangan, operasional, pemasaran, stratejik, dengan hasil menunjukkan bahwa 2 risiko dengan kategori extreme, 34 risiko dengan kategori high, 44 risiko dengan kategori medium. Dalam rangka melindungi perusahaan dari ancaman risiko serta memastikan kinerja perusahaan tetap optimal yang berlandaskan prinsip kerja efektif dan efisien, maka diperlukan adanya penerapan manajemen risiko pada perusahaan pelayaran PT XYZ.